2004
DOI: 10.1007/s10600-005-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antibacterial activities of the essential oils of stems and seeds of Pituranthos scoparius from Algerian septentrional Sahara

Abstract: and B. Ait-Kaki 2Pituranthos scoparius (Coss. & Dur.) Schinz (Umbelliferae) is a saharian species [1] used in traditional medicine for the treatment of asthma and rheumatism [2][3], Touareg people also use it in food as aroma for meal and bread [3]. The GC and GC/MS analysis of the essential oils of Pituranthos scoparius stems and seeds, collected from Ghardaia [4] (septentrional Sahara) during spring, allowed us to identify the respective components with relative percentages which appeared to be different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…To the best of our knowledge, there are very few reports available regarding the antimicrobial activity of P. scoparius essential oil. Results obtained by Boutaghane et al revealed that the essential oils extracted from stems and seeds of species collected from the region of Ghardaia (Algeria) inhibited the growth of the microorganisms namely Pseudomonas aeruginosa, Proteus mirabilis, and Klebsiella pneumonia [21].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are very few reports available regarding the antimicrobial activity of P. scoparius essential oil. Results obtained by Boutaghane et al revealed that the essential oils extracted from stems and seeds of species collected from the region of Ghardaia (Algeria) inhibited the growth of the microorganisms namely Pseudomonas aeruginosa, Proteus mirabilis, and Klebsiella pneumonia [21].…”
Section: Discussionmentioning
confidence: 99%
“…There is a distinct possibility that active principles, with differing mechanisms of action, may be present in a crude extract, thus slowing the onset of antibiotic resistance. Boutaghane et al (2004) reported a comparative study on the antibacterial activities of essential oils from stems and seeds of species collected from the region of Ghardaia (Algeria). These two kinds of essential oils inhibited the growth of the tested strains, but the seed essential oil showed lower MIC values with Proteus mirabilis, Pseudomonas aeruginosa ATCC27853, and Staphylococcus aureus ATCC25923 at 0.156 mg/ml; 1.25 mg/ml, and 20 mg/ml respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of the chemical profile of the essential oils of P. scoparius are very limited. We report mainly the work of (Vérité, Nacer, Kabouche, & Seguin, ) on stems and seeds of P. scoparius (Boutaghane et al, ) on their antibacterial activities and more recently the work of (Lograda, Ramdani, Kiram, Chalard, & Figueredo, 2013) on the variation of the essential oils compositions of P. scoparius collected from different locations in Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional use of the plant in folk medicine concerns applying it in poultices to the head for headaches (Bellakhdar, 1997). Boutaghane, Nacer, Kabouche, and Ait-Kaki (2004) reported an antibacterial activity for the seeds and stems of P. scoparius. Reports of the chemical profile of the essential oils of P. scoparius are very limited.…”
mentioning
confidence: 99%